Correlation Between Parental Knowledge About Stimulation and Speech Development in Children Aged 5-6 Years in RW 03 Air Tawar Barat Village - Laras Sati; Wirdatul 'Aini Wirdatul 'Aini (Universitas Negeri Padang, 2023)
The background of this research is the low development of speech in children, this can be seen from the fact that there are still many children who have not said sorry after making a mistake, have not said thank you and have not used the word please when asking for help. This study aims to: “1) Describe parents' knowledge about stimulation in children aged 5 to 6 years in RW 03 Air Tawar Barat Village. 2) To describe the development of speech in early childhood in RW 03, Air Tawar Barat Village. 3) Knowing the relationship between parents' knowledge about early childhood stimulation and speech development in children aged 5-6 years in RW 03, Air Tawar Barat Village.” The method used in this study is a quantitative approach with a correlational type. The population in this study were mothers who had children aged 5-6 years in RW 03 Kelurahan Air Tawar Barat, totaling 56 people. Sampling used by researchers is Cluster Random Sampling. The data collection technique used was a questionnaire. Data analysis techniques use percentage formulas and Product Moment. The results showed that: 1) The description of parents' knowledge about stimulation in RW 03 Kelurahan Air Tawar Barat was categorized as starting to develop. 2) An overview of the development of speech in children aged 5-6 years in RW 03 Kelurahan Air Tawar Barat is categorized as starting to develop well. 3) There is a significant relationship between parents' knowledge about stimulation and the development of speech in children aged 5-6 years in RW 03, Air Tawar Barat Village.